PEMOLAAN KOMUNIKASI ANAK AUTIS BERDASARKAN GANGGUAN INTERAKSI SOSIAL ATAU SYNDROMA ASPERGER - Andri Yosua Kosasih Sinambela; Nova Yohana (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
ABSTRACTThe high birth rate of children with autism in Indonesia eventually provide a variety of issues, including in the field of education. Lack of formal education means complicate the space for the children and parents of autistic orangh to obtain their rights in school. Based on the phenomenon of research objectives aim to look deeper into the characteristics of this speech community through patterning of autistic children in school Asperger syndrome Indonesian Creative School Pekanbaru.This research approach uses qualitative methods of ethnographic studies that will illustrate thoroughly and deeply associated with the speech community in this school. Data collection techniques used consisted of interviews, participant observation, and the extension of participation. As for the informants in this study the rainbow class therapists, parents of autistic children with Asperger syndrome and the school management Indonesian Creative School Pekanbaru. The results of this study indicate that there are special patterning of autistic children to interact or communicate with the environment. In particular, their communication will be different when interacting with the therapist, with the class teacher, with classmates (normal) and people you know. This is evident from the communication situation in the study where communicative events that are not based on the interest interests of children with autism will reduce acts communicative autistic children to interact with the surrounding environment.Key Words: Asperger's Syndrome, Education, Communication patterning, Ethnography of Communication Studies